Analysis of a photovoltaic-electrolyser direct-coupling system with a V-trough concentrator. (15th January 2016) - Su, Ziyun; Ding, Shuiting; Gan, Zhiwen; Yang, Xiaoyi
Highlights: A V-trough concentrator is applied in PVE system. An analysis model for the CPVE system is established and verified experimentally. The result shows that the V-trough concentrator increases the system efficiency. The hydrogen production of the PVE system is doubled in this investigation. Abstract: Hydrogen is a clean energy carrier for energy storage which is essential to solar system for continuous energy output. A promising method to store solar energy as hydrogen energy is by using photovoltaic-electrolyser (PVE) system. In this investigation, the operation of a PVE system with V-trough concentrator was studied experimentally and numerically. The V-trough concentrator was optimized and the daily average concentration ratio reaches about 1.9. A mathematical model including the sub models for irradiation flux pattern, PV array and electrolyser was established to analyze the characteristics of the system and it was verified experimentally. The results show that the utilization of V-trough concentrator makes PVE system work more efficiently with the same PV array. In this study, the conversion efficiency of solar energy to hydrogen energy was increased from 5.62% to 6.18% and the hydrogen production was doubled.